A preliminary exploration of establishing a mice model of hypoxic training - Minglu Li; Zhijie Chen; Ziyang He; Xinjuan Zhang; Yanqiu Liu; Hui Zhou; Hang Yang; Tao Liu; Xiaochuan Wang; Ran Zhang; Jiaxing Zhang (Scientific Reports)
Abstract Altitude training has been widely adopted. This study aimed to establish a mice model to determine the time point for achieving the best endurance at the lowland. C57BL/6 and BALB/c male mice were used to establish a mice model of hypoxic training with normoxic training mice, hypoxic mice, and normoxic mice as controls. All hypoxic mice were placed in a chamber filled with 16% O2 and N2, and hypoxic training mice were trained for two weeks. Then mice were removed from the chamber and tested at normoxic conditions weekly at the beginning of the experiment and the second, third, fourth, and sixth weeks. The tests for endurance ability include maximal aerobic speed (MAS), Rota-rod, and grip strength. In addition, the open field, visual cliff, and Y maze were used to test cognitive abilities. Body composition and lactic acid tolerance level were also measured. For BALB/c but not C57BL/6 mice were evaluated for effectively training. Based on the average MAS of all mice, mice successfully passed the training according to the procedure: the first week (32%MAS/10min, 48%MAS/10min, and 64%MAS/10min) and second week (40%MAS/10min, 56%MAS/10min, and 72%MAS/10min). Hypoxic training mice reached peak rotarod performance on the 7th day post-training (Test 3), with significant improvements compared to Test 1, 2, 4, and 5. At Test 3, their rotarod scores significantly differed from both H and N groups, and showing a trend towards difference from NT group. Meanwhile, hypoxic mice showed significant cognitive impairment, anxiety, depression, muscle loss, and fat gain compared with hypoxic training mice after hypoxia intervation. Two consecutive weeks of 16% O2 training followed by one week of reoxygenation may be the best for endurance competition. Thus, we think a mouse model for hypoxic training was built, with Rota-rod testing as a detection indicator. Moreover, hypoxic training may alleviate the damage of hypoxia to the body.